Perubahan Sosial Budaya Nelayan Pesisir Kedungrejo - Tianingsih, Wahyu; Sama, I Nyoman; Kaler, I Ketut (Humanis; Vol 25 No 2 (2021)DO - 10.24843/JH.2021.v25.i02.p13, 2021)
This study aims to reveal the various dynamics and attitudes of the Madurese fishing community towards changes in Kedungrejo Village. Based on the results of the analysis, this research is divided into four parts, the first is the change in Kedungrejo fishing technology from traditional to modern. Second, changes to the sea-picking ritual tradition. Third, changes in the strategy of the Kedungrejo fishing community in facing the dry season. Fourth, the attitude of the Madurese fishing community towards changes in Kedungrejo Village. Changes greatly affect the conditions that exist in the fishing community in this village, especially social and cultural values.